Causal and mediating factors for anxiety, depression and well-being. (June 2015) - Kinderman, Peter; Tai, Sara; Pontin, Eleanor; Schwannauer, Matthias; Jarman, Ian; Lisboa, Paulo
Abstract : Background: The relationship between well-being and mental ill health is complex; people may experience very low levels of well-being even in the absence of overt mental health problems. Aims: This study tested the hypothesis that anxiety, depression and well-being have different causal determinants and psychological mediating mechanisms. Method: The influence of causal and mediating factors on anxiety, depression and well-being were investigated in a cross-sectional online questionnaire survey hosted on a UK national broadcasting website. Results: Multivariate conditional independence analysis of data from 27 397 participants revealed different association pathways for the two constructs. Anxiety and depression were associated with negative life events mediated by rumination; low levels of subjective well-being were associated with material deprivation and social isolation, mediated by adaptive coping style. Conclusions: Our findings support the 'two continua' model of the relationship between psychological well-being and mental health problems, with implications for both treatment and prevention.